Southwest Research-Extension Center, Field Day 2011 (Kansas Agricultural Experiment Station Research Reports, 2011)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: crops; tillage; irrigation; weed science; insect control; SRP1052; 2011